Extraction, isolation and evaluation Trigonella foenum-graecum as mucoadhesive agent for nasal gel drug delivery - Kumar, Dharmendra; Singhal, Aditi; Bansal, Sumedha; Gupta, SK (Journal of Nepal Pharmaceutical Association, 2015)
The purpose of the study is to formulate and evaluate a new, cheap and effective natural mucoadhesive agent that can be used as an effective alternative for traditional mucoadhesive agent. The study procedure involved extraction of mucoadhesive agent from the Trigonella foenum-graecum (fenugreek) seeds, solubility testing of the mucilage obtained, phytochemical testing, determination of swelling index, preparation of nasal gel, measurement of viscosity, The study showed that the extraction of fenugreek seeds had 36% w/w of mucoadhesive agent. The natural mucoadhesive agent was soluble in hot water and cold water. The swelling index was found to be 160%.Fenugreek seeds produce high viscosity mucilage at low concentration levels. DOI: http://dx.doi.org/10.3126/jnpa.v27i1.12149 Journal of Nepal Pharmaceutical Association 2014 Vol.XXVII: 40-45